Foraging activity of Apis florea F., an important pollinator of Fennel, Foeniculum vulgare Mill. - ABROL, DHARAM PAL (ENTOMOLOGIA HELLENICA, 2025)
The foraging behaviour of fennel (Foeniculum vulgare Mill.) flower visitor insects was studied in relation to five environmental variables. Observations on insect species were made during February-March at weekly intervals throughout the flowering period. Hourly counts on individual visitors were made at the beginning of each hour, from commencement to cessation of daily activities. Among 21 visitor species, the dwarf honeybee (Apis florea) was the most abundant, accounting for more than 92.69 % of total visitors. Flight activity commenced when environmental variables surpassed a minimum threshold, while it ceased primarily due to a decline in light intensity and radiation. The foraging population showed a significant and positive correlation with air temperature, light intensity, solar radiation, and sugar concentration of nectar, and a negative correlation with relative humidity. However, path coefficient analysis revealed that the direct effect of solar radiation was high and positive, followed by air temperature and light intensity, while the direct effect of relative humidity was low and negative. The direct effect of sugar concentration of nectar was positive and negligible. Path coefficient analysis provided a clearer understanding of the effects compared to simple correlation analysis. On average, A. florea visited 7.31 ± 0.73 umbels and 19.13 ± 0.39 flowers per minute during various hours of the day. The plots pollinated by insects produced significantly more seeds with heavier weight compared to those isolated from insect visits. Fennel flowers exhibited a bimodal pattern of nectar secretion. Evidently, insect pollination needs to be encouraged for quality and quantity of seed production.